2017
DOI: 10.1016/j.heliyon.2017.e00472
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to evaluate the effects of high P rotein C omplete (l A cto) VE geta R ian (PACER) diet in non-diabetic obese Asian Indians in North India

Abstract: In view of the increasing prevalence of obesity in largely vegetarian Asian Indians, it is important to research a high protein, low carbohydrate vegetarian diet. The present study was designed to evaluate the effects of a “High Protein Complete (lacto) VEgetaRian Diet (Acronym; ‘PACER diet’), on weight, body composition and metabolic profiles in non-diabetic obese Asian Indians living in north India.In this 8-week randomized control trial, 102 vegetarian subjects with body mass index (BMI) >25 kg/m2 were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Two long‐term intervention studies from India (30 months duration) and China (6 years duration analyzed after 14 years) showed the benefits of intensive lifestyle interventions for prevention of diabetes. Other intervention trials for metabolic syndrome and obesity, predominantly in Asian Indians, also showed benefits of diet and lifestyle modifications . Despite these studies and guiding principles, public efforts for prevention remain rudimentary in most developing countries because of various challenges (Table ).…”
Section: Preventionmentioning
confidence: 99%
“…Two long‐term intervention studies from India (30 months duration) and China (6 years duration analyzed after 14 years) showed the benefits of intensive lifestyle interventions for prevention of diabetes. Other intervention trials for metabolic syndrome and obesity, predominantly in Asian Indians, also showed benefits of diet and lifestyle modifications . Despite these studies and guiding principles, public efforts for prevention remain rudimentary in most developing countries because of various challenges (Table ).…”
Section: Preventionmentioning
confidence: 99%
“…The net mean change was calculated as the mean change in the intervention group minus the mean change in the comparison group, i.e., DiD. Net relative percentage change in the outcomes was estimated in both the groups as endline mean minus baseline mean divided by the baseline mean and multiplied by 100 [33]. We conducted confirmatory hypothesis tests for the four primary outcomes, i.e., fat, sugar, salt, and fruit and vegetable intake.…”
Section: Social Networking App (Whatsapp)mentioning
confidence: 99%
“…Intervention studies with nuts in patients who have metabolic syndrome [79] and with high monounsaturated vegetable oils in patients who have NAFLD [23] have shown reductions in weight and liver fat, respectively. In vegetarians, increasing protein intake to 26.9% energy has led to a significant weight loss in Asian Indians [80]. Furthermore, meal replacement with a protein drink led to a decrease in body weight, body fat, and waist circumference, and it also had beneficial effects on metabolic parameters [81].…”
Section: Management Of Obesity In South Asiansmentioning
confidence: 99%